Pituitary apoplexy and COVID-19 vaccination: a case report and literature review - Aliberti, Ludovica; Gagliardi, Irene; Rizzo, Roberta; Bortolotti, Daria; Schiuma, Giovanna; Franceschetti, Paola; Gafà, Roberta; Borgatti, Luca; Cavallo, Michele A.; Zatelli, Maria C.; Ambrosio, Maria R. (Frontiers in Endocrinology, 2022)
A 50-year-old man was admitted to our hospital for vomit, nausea, diplopia, and headache resistant to analgesic drugs. Symptoms started the day after his third COVID-19 mRNA vaccine (Moderna) whereas SARS-CoV-2 nasal swab was negative. Pituitary MRI showed recent bleeding in macroadenoma, consistent with pituitary apoplexy. Adverse Drug Reaction was reported to AIFA (Italian Medicines Agency). A stress dexamethasone dose was administered due to the risk of adrenal insufficiency and to reduce oedema. Biochemistry showed secondary hypogonadism; inflammatory markers were elevated as well as white blood cells count, fibrinogen and D-dimer. Pituitary tumour transsphenoidal resection was performed and pathology report was consistent with pituitary adenoma with focal haemorrhage and necrosis; we found immunohistochemical evidence for SARS-CoV-2 proteins next to pituitary capillaries, in the presence of an evident lymphocyte infiltrate. Few cases of pituitary apoplexy after COVID-19 vaccination and infection have been reported. Several hypotheses have been suggested to explain this clinical picture, including cross-reactivity between SARS-CoV-2 and pituitary proteins, COVID-19-associated coagulopathy, infection-driven acutely increased pituitary blood demand, anti-Platelet Factor 4/heparin antibodies development after vaccine administration. Ours is the first case of SARS-CoV-2 evidence in pituitary tissue, suggesting that endothelial infection of pituitary capillaries could be present before vaccination, possibly due to a previous asymptomatic SARS-CoV-2 infection. Our case underlines that SARS-CoV-2 can associate with apoplexy by penetrating the central nervous system, even in cases of negative nasal swab. Patients with pituitary tumours may develop pituitary apoplexy after exposure to SARS-CoV-2, therefore clinicians should be aware of this risk.